The Correlation between Students’ Reading Comprehension and Their Writing Skill at MTsN 5 Pandeglang - Veny Agustini Prianggita; Mochammad Habibi (Journal of English Education Studies, 2018)
This study discusses the ability to read and write. The study aims to answer some problems, namely: 1) Knowing students’ reading comprehension, 2) Knowing students’ writing skill, and 3) To obtain whether there is a significant relationship between students' reading comprehension and writing skills or not. This research uses Mix method. The population is 183 students of MTs. Negeri 5 Pandeglang. The researcher took 30 students as sample. To test the research hypothesis, the researcher collected data analysis using inferential statistical techniques using Product Moment formula. The finding of research hypothesis shows that: 1) The level of students’ comprehension in reading was very low. This could be seen from the analysis that shows the mean 59.7. 2) The level of students’ writing skill was in the medium category. This could be seen from the analysis, showing the mean 68. 3) There is a significant positive relationship between reading ability and writing ability. Based on the quantitative analysis, the results of the research show that the observation value r is 0.963 above the 5% rejection limit of 0.361 and the 1% rejection limit of 0.461, in other words 0.963 > 0.463 at the 5% level and 0.361 > 0.963 at the 1% level. Thus the result is stated significant and the proposed hypothesis is accepted.